2022
DOI: 10.3389/fendo.2022.895512
|View full text |Cite
|
Sign up to set email alerts
|

Intensity Dependent Effects of Interval Resistance Training on Myokines and Cardiovascular Risk Factors in Males With Obesity

Abstract: ObjectiveTo determine the effects of different intensities of interval resistance training (IRT) protocols on the levels of select myokines (decorin, follistatin, myostatin, activin A, transforming growth factor beta-1 [TGF-β1]), and cardiometabolic and anthropometric measures in males with obesity.MethodsForty-four obese males (age: 27.5 ± 9.4 yr.; height: 165.4 ± 2.8 cm; weight: 97.9 ± 2.6 kg and BMI: 35.7 ± 4.3 kg/m2) were randomly assigned to one of four groups (n=11 per group): low-intensity interval resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…In this regard, Nasiri et al reported that eight weeks of Pilates training had no significant impact on serum DCN (24). Ataeinosrat et al also concluded that low-intensity resistance training had no influence on serum DCN, but moderate and high-intensity training increased it in rats (25).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Nasiri et al reported that eight weeks of Pilates training had no significant impact on serum DCN (24). Ataeinosrat et al also concluded that low-intensity resistance training had no influence on serum DCN, but moderate and high-intensity training increased it in rats (25).…”
Section: Discussionmentioning
confidence: 99%
“…After collection, the tubes were gently shaken five times for thorough mixing, and then the samples were placed on ice and refrigerated. After collecting blood from all participants, the blood collection tubes were centrifuged at 3000 r/min and 4 °C for 10 min to separate the plasma 26 . The Architect C-8000 (Abbott Laboratories, USA) automated chemistry analyzer was utilized to measure total cholesterol (TC), triglycerides (TG), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), alanine aminotransferase (ALT), and uric acid (UA) 27 .…”
Section: Methodsmentioning
confidence: 99%
“…A study found low-intensity interval resistance training can lead to beneficial changes in myokines [ 65 ]. In this study, subjects performed resistance training for 12 weeks, with 40% 1RM and 15 to 20 repetitions [ 65 ].…”
Section: Can Exerkines (Generated/stimulated By Physical Activity/phy...mentioning
confidence: 99%
“…A study found low-intensity interval resistance training can lead to beneficial changes in myokines [ 65 ]. In this study, subjects performed resistance training for 12 weeks, with 40% 1RM and 15 to 20 repetitions [ 65 ]. However, low-intensity physical exercise of 20–40 Vo 2max or 35–45% of HR max , such as running, cycling, or walking, for less than five weeks appears not to affect myokines [ 30 , 31 , 32 , 34 ].…”
Section: Can Exerkines (Generated/stimulated By Physical Activity/phy...mentioning
confidence: 99%